Novel availability and integrity verification protocol for ISMAC system under cloud environment. (January 2017) - Li, Jun
Abstract: The Novel Availability and Integrity Verification Protocol (NAIVP) is a novel technique for indicating the global availability and general integrity that is supported by data that has been stored in the cloud. There are several schemes that have been designed which rely on the Vandermonde-based Reed-Solomon Code. This is necessary to ensure that the data has good availability. Researchers have proposed the homomorphic distributed verification protocol for guaranteeing the security of data storage in the cloud and pseudorandom data is used by the token pre-computation to determine whether the stored data is correct. However, there is very little integrity in the security provided for the data. The proposed NAIVP overcomes the difficulties faced by this previously published protocol. It can offer robust assurance of the availability and integrity of information stored in the cloud using fractional dynamic data sustenance through verifiability. The experimental result proves effectiveness and robustness of the proposed methodology.